Decomposing educational inequality in maternal mortality in Iran. Issue 3 (16th March 2021) - Amini-Rarani, Mostafa; Mansouri, Asieh; Nosratabadi, Mehdi
ABSTRACT: Given the significance of educational equality as one of the key social determinants of health in maternal health outcomes, the present study aimed to assess maternal mortality inequality and its main contributors based on the level of education amongst mothers living in Isfahan, Iran. In this case–control study, all 171 maternal deaths in the Isfahan Province during 2001–2016 were taken from the national maternal mortality surveillance system (as a case group). For the control group, 523 mothers who were alive were selected from 22 health centers located in 21 cities in the province of Isfahan. Concentration index and curve were used to measure educational inequality in maternal mortality. The chi-square test was used to select explanatory social and health variables to enter the decomposition model. The analyses were performed with STATA 12. Social and healthcare factors accounted for 43.57% and 23.44% of educational inequality, respectively. The normalized maternal mortality concentration index was −0.13 (95% CI, −0.10 to −0.02). Among the social factors, the mother's education level (38.14%) and immigrant status (25.39%) contributed the most to educational inequality. Regarding healthcare factors, proximate medical causes (14.49%) and the number of pregnancies (9.72%) had the highest contribution. Maternal mortality has been distributed unequally among the less and more educated mothers in Iran, which suggests that promoting health literacy is imperative, especially for women with lower education levels.